2015
DOI: 10.1016/j.envres.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the physical health impacts from non-occupational exposure to wildfire smoke

Abstract: Background Climate change is likely to increase threat of wildfires, and little is known about how wildfires affect health in exposed communities. A better understanding of the impacts of the resulting air pollution has important public health implications for the present day and the future. Method We performed a systematic search to identify peer-reviewed scientific studies published since 1986 regarding impacts of wildfire smoke on health in exposed communities. We reviewed and synthesized the state of sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
449
1
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 468 publications
(502 citation statements)
references
References 105 publications
(181 reference statements)
13
449
1
18
Order By: Relevance
“…This epidemiologic evidence helps strengthen the association between wildfire smoke exposure and cardiovascular disease outcomes and highlights the increased risk to the older population. These findings, along with others, support the need for clinical research to assess the clinical and public health value of interventions to decrease exposure to particulate matter, and particularly to wildfire smoke, among those at highest risk 11, 12, 55, 57, 58, 59. As wildfire season intensity and duration is projected to increase in California, understanding adverse health impacts of wildfire smoke and identifying the most susceptible populations is relevant to a broad group of stakeholders, including state and local officials responsible for land and air quality management, environmental scientists, policy makers, public health officials, and frontline public health and healthcare practitioners.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…This epidemiologic evidence helps strengthen the association between wildfire smoke exposure and cardiovascular disease outcomes and highlights the increased risk to the older population. These findings, along with others, support the need for clinical research to assess the clinical and public health value of interventions to decrease exposure to particulate matter, and particularly to wildfire smoke, among those at highest risk 11, 12, 55, 57, 58, 59. As wildfire season intensity and duration is projected to increase in California, understanding adverse health impacts of wildfire smoke and identifying the most susceptible populations is relevant to a broad group of stakeholders, including state and local officials responsible for land and air quality management, environmental scientists, policy makers, public health officials, and frontline public health and healthcare practitioners.…”
Section: Resultssupporting
confidence: 63%
“…One recent review found that most studies with combined cardiovascular outcomes have found no significant associations, although some specific outcomes have been shown to be increased in the context of wildfire smoke, such as out‐of‐hospital cardiac arrest, heart failure, and ischemic heart disease 11. Another review found that 6 of 14 studies revealed statistically significant associations of wildfires and cardiovascular outcomes 12. Since the publication of that review, however, at least 4 subsequent investigations have identified elevated risk of cardiovascular events associated with wildfire smoke exposure, which may reflect recent use of more sophisticated methods or utilization of more specific outcomes 15, 20, 26, 42…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wildfires occur annually in Oregon, and the health risks of wildfire smoke are well documented 1 . Before implementing syndromic surveillance through Oregon ESSENCE, assessing the health effects of wildfires in real time was very challenging.…”
Section: Introductionmentioning
confidence: 99%